Using Canva Videos as an Alternative Learning Bank Lesson from Indonesia - Nasrulloh, Ubaid Fandi; Chamoli, Anjana (Indonesian Scientific Publication, 2024)
The use of ICT in the learning process is a problem and challenge for educators, especially since the use of this technology must be collaborated with the application of learning models. This research aims to produce a product in the form of a Canva learning video based on the Discovery Learning learning model that is suitable for use and provides effectiveness for student learning outcomes. The method used is the Research and Development (R&D) method with the Borg and Gall development model, which includes seven stages, namely: 1) Preliminary Study, 2) Planning, 3) Initial product manufacture, 4) Preliminary field test, 5) Main product revision, 6) Main field trial, 7) Operational product revision. The method of analyzing qualitative and quantitative descriptive data is a linker scale and N-Gain value test. Based on the results of the study, it was found that the feasibility of Canva learning video media by media experts was 100% with the criteria of